Qualities of a Good and Effective Teacher: Slovak EFL Pre-Service and In-Service Teachers' Perspectives - Rastislav Metruk (National Research University Higher School of Economics, 2020)
A plethora of researchers have attempted to examine the characteristics of a good and effective teacher in order to enhance the process of teaching foreign languages. In line with those explorations, this study aims at performing a comparison between Slovak pre-service EFL (English as a foreign language) teachers' and Slovak in-service EFL teachers' perceptions of a good and effective language teacher. To achieve this objective, a convenient sample of Slovak university EFL students who were pre-service teachers (n = 74) and Slovak lower-secondary and upper-secondary school teachers (n = 63) were employed in the study. Using a 57-item Likert-type questionnaire, independent-samples t-tests were conducted to investigate the potential differences between the perceptions of the pre-service teachers and in-service teachers. Moreover, the 10 highest-mean and 10 lowest-mean items of both groups were analyzed. The research results revealed that statistically significant differences (p ≤ 0.05) were detected in only 12 of the 57 items. Furthermore, a closer examination of the differences and the items with the highest and lowest means indicated that the pre-service teacher participants favored traditional teaching more than their in-service teacher counterparts, who preferred CLT (Communicative Language Teaching) to a greater extent. The potential implications of these findings indicate that the fundamental principles of CLT such as employing plenty of pair-work and group-work activities, facilitating learners' autonomy and responsibility for their own learning, or varying classroom interaction strategies deserve more careful attention during pre-service teacher training.